2022
DOI: 10.1109/tns.2022.3148579
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation Effects in Silicon Photonics Modulators

Abstract: Silicon Photonics shows considerable potential as a radiation-hard technology for building the optical data transmission links for future high-energy physics experiments at CERN. Optical modulators are a key component of optical links, which will need to withstand radiation doses in excess of 10 MGy. The geometrical parameters and doping concentrations of two popular types of Silicon Photonics modulators, Mach-Zehnder and Ring Modulators, have been varied in order to study their impact on the device radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Silicon photonics has been identified as an excellent candidate for the development of the next generation of high-speed data links for high energy physics experiments. It has potential for the realisation of low-power and highly-integrated systems, without optical and electrical interference between Tx and Rx, as well as proven TID tolerance beyond 10 MGy [11]. A SiPh Tx test board based on RMs has been developed, and in this work we demonstrated that the modulator can be driven by CML signals, like the lpGBT Tx output.…”
Section: Discussionmentioning
confidence: 84%
“…Silicon photonics has been identified as an excellent candidate for the development of the next generation of high-speed data links for high energy physics experiments. It has potential for the realisation of low-power and highly-integrated systems, without optical and electrical interference between Tx and Rx, as well as proven TID tolerance beyond 10 MGy [11]. A SiPh Tx test board based on RMs has been developed, and in this work we demonstrated that the modulator can be driven by CML signals, like the lpGBT Tx output.…”
Section: Discussionmentioning
confidence: 84%
“…fibre links, in terms of link length (reach), bandwidth, and power consumption. Ring modulators have shown excellent tolerance to Total Ionising Dose (TID), up to 1 Grad [10]. Figure 2 shows two optical eye diagrams produced using a ring modulator integrated on our test PIC when driven by a commercial driver with 1 V pp modulation voltage.…”
Section: Jinst 18 C03002mentioning
confidence: 99%
“…In this context, the pressing need to find alternative technologies for the evolution of radiation-hard optical links has led to the evaluation of silicon photonics (SiPh) [9]. SiPh components have indeed recently demonstrated impressive radiation tolerance thanks to the application of proper design hardening techniques and annealing procedures [10][11][12][13][14][15]. Although being still under deeper investigation regarding the stability of radiation -1 -…”
Section: Introductionmentioning
confidence: 99%